2017
DOI: 10.12913/22998624/76481
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Structure and Shear/Peel Strength of Refill Friction Stir Spot Welded 7075-T6 Aluminium Alloy Joints

Abstract: The article presents an analysis of the macrostructure and mechanical properties of spot welds of joints made by Refill Friction Spot Stir Welding (RFSSW) method. RFSSW is a relatively new technology that is gaining wider use, not only in the automotive and aviation industries because it is a less energy intensive method than resistance spot welding. The primary focus of the article is the effect of welding time on the quality of the welded joints of sheet metal using the aforementioned method. The research wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Additionally, material flow was aided by the material's softening as a result of the increasing temperatures in the SZ with the increase in RS. Increased temperatures allow proper phase change and enhance metallurgical bonding between weldments [33,57]. According to the experimental results, the PR parameter had the least influence on joint strength [31].…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Additionally, material flow was aided by the material's softening as a result of the increasing temperatures in the SZ with the increase in RS. Increased temperatures allow proper phase change and enhance metallurgical bonding between weldments [33,57]. According to the experimental results, the PR parameter had the least influence on joint strength [31].…”
Section: Resultsmentioning
confidence: 92%
“…PR/welding time (WT) is the parameter with the least influence on joint strength [18,22,24,31]. In most of the earlier work, it was observed that joint strength is enhanced with an increase in the WT/decrease in PR [8,10,27,32,33]. The increased WT allows a rise in temperature for proper phase change of the material and improves material flowability and mixing.…”
Section: Introductionmentioning
confidence: 99%
“…Materials from one batch were used for testing. The selection of the parameter range was carried out on the basis of preliminary tests [19]. On their basis, it was found that the welding time in the range of 1-1.5 s does not significantly affect the LC of the obtained joints.…”
Section: Methodsmentioning
confidence: 99%
“…In order to more fully analyze the effect of tool depth on weld properties, the plan was extended by one level of the input factor x2 (Figure 3). The selection of the parameter range was carried out on the basis of preliminary tests [19]. On their basis, it was found that the welding time in the range of 1-1.5 s does not significantly affect the LC of the obtained joints.…”
Section: Methodsmentioning
confidence: 99%